ANALISIS TANTANGAN DAN EVALUASI PENYELENGARAAN PROGRAM PENDIDIKAN MASYARAKAT - Ivana Anelia Samosir; Esra Siagian; Musniari Sitanggang (Universitas Negeri Medan, 2026)
This study evaluates the implementation of a community education program within a private tutoring institution and critically examines the dilemma between educational commercialization and inclusivity principles at Qualifa House Tutoring Institution in Deli Serdang Regency, Indonesia. A descriptive qualitative approach was employed using observations, in-depth interviews, and document analysis. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña based on seven core principles of community education: participation, relevance, sustainability, equity, independence, openness, and flexibility. The findings reveal that the principles of relevance, flexibility, and independence were strongly implemented through learner-centered programs that responded effectively to participants’ educational needs and encouraged self-directed learning. However, the principle of equity emerged as the weakest dimension due to limited access for learners from low-income families caused by a fee-based financing system. In addition, participation, sustainability, and openness were found to be moderately implemented because of limited community involvement, insufficient external partnerships, and weak program accountability mechanisms. These findings highlight a fundamental tension between organizational sustainability and equitable educational access. The study concludes that lembaga bimbingan belajaroperating within community education contexts require a social entrepreneurship model capable of balancing financial sustainability with social inclusion